2013
DOI: 10.1017/s0016756812000921
|View full text |Cite
|
Sign up to set email alerts
|

Carboniferous floras in siliciclastic rocks of Kashmir Himalaya, India and the evolutionary history of the Tethyan Basin

Abstract: The Fenestella Shale Formation of Jammu and Kashmir Himalaya comprises latest Viséan or Serpukhovian siliciclastic deposits formed along the southern margins of the Palaeotethys Ocean. A sequence of shallowing upward and deepening upward units indicates changes from shoreface to offshore and deeper shelf conditions, probably controlled by eustatic changes in an otherwise passive depositional system. Some of the finer-grained, shallow marine deposits have yielded fossil floras dominated by sub-arborescent lycop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Carboniferous Calamospora is known in situ from strobili of Equisetales (e.g., Calamostachys and Palaeostachya ) and Sphenophyllales ( Bowmanites ), and cones belonging to Noeggerathiales, of unknown affinity (Balme, 1995; Taylor, Taylor, & Krings, 2009). However, there is quite a possibility that the Calamospora reported herein might have been produced from Noeggerathiales or Sphenophyllales group of plants, as these are abundant in the Carboniferous macroflora of Kashmir and Spiti (Saxena, Singh, Cleal, Gupta, & Bali, 2019; K. J. Singh et al, 2013) (Table 3).…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Carboniferous Calamospora is known in situ from strobili of Equisetales (e.g., Calamostachys and Palaeostachya ) and Sphenophyllales ( Bowmanites ), and cones belonging to Noeggerathiales, of unknown affinity (Balme, 1995; Taylor, Taylor, & Krings, 2009). However, there is quite a possibility that the Calamospora reported herein might have been produced from Noeggerathiales or Sphenophyllales group of plants, as these are abundant in the Carboniferous macroflora of Kashmir and Spiti (Saxena, Singh, Cleal, Gupta, & Bali, 2019; K. J. Singh et al, 2013) (Table 3).…”
Section: Resultsmentioning
confidence: 95%
“…Their presence in the Lingti section proves that either Cordaites or some other Cordaitalean genera were growing at that time in the surrounding areas. K. J. Singh et al (2013) have reported the occurrence of cf. Cordaites leaf from the Early Carboniferous Fenestella Shale Formation of Kashmir.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations